A revised checklist of mosquitoes Genus Coquillettidia Dyar, 1905 (Diptera: Culicidae) from Indonesia with key to species - Sidiq Setyo Nugroho; Mujiyono Mujiyono; Fahmay Dwi Ayuningrum; Riyani Setiyaningsih; Upiek Ngesti Wibawaning Astuti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Nugroho SS, Ayuningrum FD, Setyaningsih RS, Astutu UNW. 2020. A revised checklist of mosquitoes Genus Coquillettidia Dyar, 1905 (Diptera: Culicidae) from Indonesia with key to species. Biodiversitas 21: 5772-5777. Mosquito species from Genus Coquillettidia are mostly found in Afrotropic Region, with some species distributed in the Oriental and Australasian Region including Indonesia. Some species are confirmed as the vector for human pathogens. As previous research stated that up to 1981, there were eight species of Coquillettidia that have been on the checklist of mosquitoes in Indonesia. Nowadays, eleven Coquillettidia species present in Indonesia entirely included in Subgenus Coquillettidia. Three species were added to the checklist, namely Cq. fuscopteron Theobald, Cq. novochracea Barraud, and Cq. xanthogaster Edwards. Research and publication about Genus Coquillettidia in Indonesia are still rare, besides that, the identification key of Coquillettidia female mosquito in Indonesia has never been published before. This paper intended to deliver information about the species checklist and distribution of Genus Coquillettidia in Indonesia and provide a species identification key for female mosquitoes.